The placemakers' guide to building community - Hamdi, Nabeel (London ; Washington, DC : Earthscan, 2010)
This is a guide to placemaking, packed with practical skills and tools that architects, planners, urban designers and other built environment specialists need in order to engage effectively with development work in any context.
Includes bibliographical references and index.
Keywords: Community development -- Developing countries; Economic development -- Developing countries; Human settlements -- Developing countries; City planning -- Developing countries